An Outcomes Review of 330 Sternal Wound Reconstructions: Timing of Closure Does Make a Difference. Issue 2 (August 2021) - Levy, Adam S.; Altchek, Chloe L.; McMillen, Elizabeth M.; Karinja, Sarah J.; Tiao, Jonathan R.; Smith, Craig R.; Ascherman, Jeffrey A.
Abstract : Background: Sternal wound infection and dehiscence following cardiac surgery remain difficult clinical problems with high morbidity. Older classification systems regarding timing to reconstruction do not take into account recent improvements in critical care, wound vacuum-assisted closure use, or next-generation antibiotic therapies, which may prolong time to reconstruction. Methods: Records of patients undergoing sternal wound reconstruction performed by the senior author (J.A.A.) from 1996 to 2018 at a high-volume cardiac surgery center were reviewed. Indications included sternal wound infection or dehiscence. All patients underwent single-stage removal of hardware, débridement, and flap closure. Patients were divided into two groups based on timing of wound closure after cardiac surgery: less than 30 days or greater than or equal to 30 days. Results: Of the 505 patients identified during the study period, 330 had sufficient data for analysis. Mean time to sternal wound surgery was 15.7 days in the early group compared to 64.4 days ( p < 0.01) beyond 30 days. Postdébridement cultures were positive in 72 percent versus 62.5 percent of patients ( p = 0.11), whereas rates of postoperative infection were significantly higher in the delayed group: 1.9 percent versus 9.5 percent ( p < 0.01). Partial wound dehiscence rates were also higher after 30 days (1.9 percent versus 11.3 percent; p < 0.01), whereas total length of stay was decreased. Use of wound vacuum-assisted closure was significantly associated with reconstruction beyond 30 days ( p < 0.01). Conclusions: Although performing sternal wound reconstruction more than 30 days after initial cardiac surgery was associated with a shorter overall hospital length of stay and higher extubation rates in the operating room, these patients also had elevated postoperative infection and wound complication rates. The authors thus recommend not delaying definitive surgical reconstruction when possible. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.